International history and the study of public opinion: towards methodological clarity - Hucker, Daniel (Taylor & Francis (Routledge), 2012)
International historians have long been fascinated by public opinion and its influence on policymaking, citing it frequently as one of the many factors that inform foreign policy choices. However, historians – and international historians in particular – have yet to develop any substantial or rigorous methodological frameworks capable of revealing the actual influence of popular opinion at the highest levels of diplomatic policy. This article intends to redress this deficiency by outlining a methodological approach that elucidates the role of public opinion in the decision-making process. In so doing, it will also explore the tensions between different approaches to the study of international history, notably the apparent divergence between traditional ‘diplomatic’ history on the one hand and the more theoretically-diffuse ‘international’ history on the other. The conceptual framework forwarded here will suggest that the two approaches need not be in opposition, at least when seeking to explain the formative role of public opinion on foreign policymaking. Indeed, the careful application of inter-disciplinary theoretical frameworks not only enriches our understanding of international history in its totality, but also reveals much about the diplomatic fulcrum of our discipline.